2018
DOI: 10.1016/j.xphs.2017.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Solid Dispersion of Meloxicam Enhanced Oral Absorption in Rats With Impaired Gastric Motility

Abstract: Meloxicam (MEL) shows a slow onset of action in severe pain patients on account of delayed gastric motility. This study aimed to develop an amorphous solid dispersion (ASD) of MEL to achieve rapid oral absorption in severe pain patients. ASD formulations of MEL with hydroxypropylmethylcellulose (ASD-MEL/HPMC) and polyacrylates and polymethacrylates (ASD-MEL/EUD) were prepared and physicochemically characterized. Oral absorption behavior of MEL samples was also clarified in both normal and propantheline (PPT)-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 28 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…SDs of meloxicam exhibited much better dissolution behavior than crystalline meloxicam. It was reported that meloxicam was presented in the amorphous form by SDs which lead to its improved dissolution behavior [ 5 ]. Prepared SDs of chlortetracycline hydrochloride using hydrophilic polymers like PVP and copovidone, Authors reported that SDs increased almost ten-fold chlortetracycline hydrochloride solubility, which they attributed to the amorphous characters of the SDs, proposing the event of intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…SDs of meloxicam exhibited much better dissolution behavior than crystalline meloxicam. It was reported that meloxicam was presented in the amorphous form by SDs which lead to its improved dissolution behavior [ 5 ]. Prepared SDs of chlortetracycline hydrochloride using hydrophilic polymers like PVP and copovidone, Authors reported that SDs increased almost ten-fold chlortetracycline hydrochloride solubility, which they attributed to the amorphous characters of the SDs, proposing the event of intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…28) Many in vivo studies during preclinical study adopt a suspension form for oral administration. [29][30][31] We observed, during in vitro dissolution, FEN supersaturation evidenced by the dissolution of the clinical ASD formulation of FEN (Tricor ® Tablets) followed by a rapid decrease in concentration, indicating precipitation (Fig. 1).…”
Section: Discussionmentioning
confidence: 89%
“…The largest and the smallest stability constants were observed at phosphate buffer pH 7.4 and at pH 1.2, as depicted in Table 1 . This result could be attributed to the weak acidity nature of the ME which formed a zwitterionic compound with two lower pKa values 1.09 and 4.18 and the solubility in both around 0.6 µg/mL [ 33 ]. For that, ME has a higher solubility in basic conditions and low solubility in acidic media.…”
Section: Resultsmentioning
confidence: 99%
“…It has poor aqueous solubility and higher permeability, which fall under class II medications in biopharmaceutical classes systems. However, the poorly aqueous solubility and wettability of ME resulted in a slower dissolution rate of the drug, and hence, a lower oral bioavailability concomitant with slowing its onset of action [ 33 , 34 ]. Enhancing the aqueous solubility of ME could facilitate its oral absorption and bioavailability and reduce its onset of action for the treatment of different types of acute pain [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%